2020
DOI: 10.1021/acs.langmuir.0c02396
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-Modified AuCu Bimetallic Nanoclusters as Charge Transfer-Based Biosensors for Highly Sensitive Glycine Detection

Abstract: Glycine is the simplest amino acid in living organisms and plays important roles in biology and medicine. However, few biosensors for glycine sensing have been reported. Herein, we present a facile strategy to construct dopaminemodified AuCu bimetallic nanoclusters (denoted as AuCu NC− DA) as charge transfer-based biosensors for highly sensitive glycine sensing. The AuCu NCs stabilized by bovine serum albumin (BSA) exhibited a fluorescence maximum at 400 nm. Because of the high affinity of BSA for dopamine (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…AuCu nanoparticles are known to exhibit fluorescence and are used for this reason in sensing applications. 69,70 In addition to UV-vis spectral changes, shifts in the photoluminescence spectra give additional insights that correlate to differences in the alloyed AuCu cluster–TPP ligand interaction as compared to the monometallic Au cluster–ligand interaction. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AuCu nanoparticles are known to exhibit fluorescence and are used for this reason in sensing applications. 69,70 In addition to UV-vis spectral changes, shifts in the photoluminescence spectra give additional insights that correlate to differences in the alloyed AuCu cluster–TPP ligand interaction as compared to the monometallic Au cluster–ligand interaction. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[147][148][149][150][151] Compared to metal NCs comprised of a single metal, BMNCs comprised of heterometals in their system possess better cooperative electronic, optical, sensing and biological properties. 102,138,[152][153][154][155] This section discusses the synthetic procedures available to synthesize metal-based luminescent nanomaterials.…”
Section: Synthetic Methods For Luminescent Gold Nanomaterialsmentioning
confidence: 99%
“…In addition to Au–Ag, other examples of bimetallic systems that have been prepared via BSA-mediated synthesis are Au–Cu, Au–Ni, Au–Pt, and Pt–Bi. Meanwhile, lysozyme is another protein aside from BSA that has been found useful in the protein-directed synthesis of Au–Ag nanoclusters . Other related studies involve peptides with much shorter amino acid chains than proteins. , As an example, Wang et al made use of glutathione (GSH), a peptide comprised of only three amino acids, to synthesize composition-tunable Au–Ag nanoclusters via the galvanic replacement route …”
Section: Biogenic Synthesismentioning
confidence: 99%
“…135 Chen et al demonstrated that through surface modification with dopamine, BSA-capped Au−Cu nanoclusters can be used as a fluorescent biosensor for glycine detection based on an off/on fluorescence switching behavior. 99 The fluorescence of the presynthesized BSA-capped nanoclusters was switched off after modification with dopamine as a result of a charge transfer process. In the presence of glycine, this charge transfer process was inhibited due to hydrogen bonding interactions, thereby turning on the fluorescence.…”
Section: Applications In Catalysis and Sensingmentioning
confidence: 99%